Transition-Metal-Catalyzed C–H Activation Reactions for the Creation and Modification of Organic Fluorophores - Chand, Tapasi; Kapur, Manmohan (Synthesis, 2024)
Organic fluorophores have consistently garnered significant interest owing to their widespread application across various multidisciplinary research fields. In the realm of biological research, these organic fluorophores find extensive use in diverse applications such as molecular imaging, DNA sequencing, drug discovery, and biosensors. Remarkably, in recent times, organic fluorescent molecules have emerged as pivotal elements in the advancement of organic electronics. Across several reaction pathways developed for constructing and modifying organic fluorophores, transition-metal-catalyzed C–H activation reactions have come across as a dependable and step-economical approach. In this review we discuss various transition-metal-catalyzed C–H activation-based approaches that have been employed to create and modify organic fluorescent molecules which find applications in multidisciplinary research areas.1 Introduction2 Basic Reactions for the Creation of Organic Fluorophores3 Merits and Drawbacks of Classical Reactions in the Creation and Modification of Organic Fluorophores4 C–H Activation/Functionalization Reactions5 C–H Activation Pathways in the Creation and Modification of Organic Fluorophores5.1 Electrophilic C–H Activation Reactions5.2 Heteroatom-Directed C–H Activation Reactions6 Conclusion
Keywords: organic fluorophores; transition metal catalysis; C–H activation; annulation; C–H functionalization